Comparative Evaluation of Different Mint Species Based on Their In Vitro Antioxidant and Antibacterial Effect - Ameni Sfaxi; Szilvia Tavaszi-Sárosi; Kovács Flórián; Katalin Patonay; Péter Radácsi; Ákos Juhász (Plants)
In our research six different mint species (peppermint, spearmint (five different chemotypes), Horse mint, mojito mint, apple mint (two different chemotypes), bergamot mint) have been evaluated by referring to their chemical (essential oil (EO) content and composition) and in vitro biological (antibacterial, antioxidant effect) characteristics. The EO amount of the analyzed mint populations varied between 1.99 and 3.61 mL/100 g d.w. Altogether, 98 volatile compounds have been detected in the oils. Antibacterial effects (inhibition zones, MIC, IC50 and MBC) were evaluated against Escherichia coli, Salmonella enterica, Bacillus cereus and Staphylococcus aureus. The best antibacterial effect was given by a carvacrol–thymol chemotype spearmint population (inhibition zone: 18.00–20.00 mm, MIC: 0.06 v/v%, IC50: 0.01–0.03 v/v%, MBC: 0.06, >2.00 v/v%). The least effective oil in the case of Gram-negative bacteria was bergamot mint (inhibition zone: 7.67–8.67 mm, MIC: 2.00, >2.00 v/v%, IC50: 0.11–0.25 v/v%, MBC: 2.00, >2.00 v/v%), while in the case of Gram-positive bacteria, oils containing dihydrocarvone as the main compound possessed the weakest antibacterial effect (inhibition zone: 9.00–10.00 mm, MIC: 1.00–2.00 v/v%, IC50: 0.22–0.37 v/v%, MBC: >2.00 v/v%). Interestingly, none of the oils could kill B. cereus in the applied concentrations.